Antimicrobial and Antibiofilm Potential of Flourensia retinophylla against Staphylococcus aureus - Minerva Edith Beltrán-Martínez; Melvin Roberto Tapia-Rodríguez; Jesús Fernando Ayala-Zavala; Agustín Gómez-Álvarez; Ramon Enrique Robles-Zepeda; Heriberto Torres-Moreno; Diana Jasso de Rodríguez; Julio César López-Romero (Plants, 2024)
Staphylococcus aureus is a Gram-positive bacteria with the greatest impact in the clinical area, due to the high rate of infections and deaths reaching every year. A previous scenario is associated with the bacteria’s ability to develop resistance against conventional antibiotic therapies as well as biofilm formation. The above situation exhibits the necessity to reach new effective strategies against this pathogen. Flourensia retinophylla is a medicinal plant commonly used for bacterial infections treatments and has demonstrated antimicrobial effect, although its effect against S. aureus and bacterial biofilms has not been investigated. The purpose of this work was to analyze the antimicrobial and antibiofilm potential of F. retinophylla against S. aureus. The antimicrobial effect was determined using an ethanolic extract of F. retinophylla. The surface charge of the bacterial membrane, the K+ leakage and the effect on motility were determined. The ability to prevent and remove bacterial biofilms was analyzed in terms of bacterial biomass, metabolic activity and viability. The results showed that F. retinophylla presents inhibitory (MIC: 250 µg/mL) and bactericidal (MBC: 500 µg/mL) activity against S. aureus. The MIC extract increased the bacterial surface charge by 1.4 times and the K+ concentration in the extracellular medium by 60%. The MIC extract inhibited the motility process by 100%, 61% and 40% after 24, 48 and 72 h, respectively. The MIC extract prevented the formation of biofilms by more than 80% in terms of biomass production and metabolic activity. An extract at 10 × MIC reduced the metabolic activity by 82% and the viability by ≈50% in preformed biofilms. The results suggest that F. retinophylla affects S. areus membrane and the process of biofilm formation and removal. This effect could set a precedent to use this plant as alternative for antimicrobial and disinfectant therapies to control infections caused by this pathogen. In addition, this shrub could be considered for carrying out a purification process in order to identify the compounds responsible for the antimicrobial and antibiofilm effect.